The Strategy Of Sovietizing Public Education In The Uzbek Ssr: Based On The Materials Of The Journal “Maorif Va Oʻqitgʻuchi” Of 1925 - Yaminxon Muxammedovich Askarxodjayev (Periodica Journal, 2025)
The following article is dedicated to the analysis of the collection of decrees and resolutions in the 3rd issue of the journal “Maorif va oʻqutgʻuchi” (“Education and teacher”) published in 1925. The analysis aims to study the ideological-political, personnel policy-related, and economic-financial foundations for the radical reform of public education in the early Soviet period in the Uzbek SSR. The article reveals the aspirations to orient education based on class principles, as well as the contradictions that arose in practice concerning the quality of personnel and financial stability. Based on additional sources, the historical context of the documents and their significance in the Soviet literacy campaign (Likbez) are highlighted
Keywords: Public education; Sovietization; personnel policy; financial control